PERLINDUNGAN HUKUM TERHADAP HAK-HAK MASYARAKAT DESA DALAM KAJIAN TERHADAP UU NO. 6 TAHUN 2014 TENTANG DESA - Rif’ah, Emi Badriatur; Ilmiah, Fitayatul; Mushafi, Mushafi (Legal Studies Journal, 2023)
This research examines legal protection for the rights of village communities. The focus of this study is Law no. 6 of 2014 concerning Villages. The type of research method that will be used in this research is in the category of normative legal research. Because normative research mainly uses library materials as a source of research data. or also called (Library research), a method used to collect data from various literature. This research approach is a conceptual approach and conceptual approach. The results of this research state that, firstly, the rights of village communities are an authority or power granted by law. An interest that is protected by law, both private and public, secondly legal protection, the village government has the obligation to fulfill the rights that have been regulated in the Village Law. However, what is not regulated in the Village Law is the regulation of legal protection if these rights are not granted, resulting in legal uncertainty.